Consumer Preferences for Cut Roses and the Effect of the Introduction of a New Cultivar on the US Market - Andres M. Mayorga-Gomez; Julie H. Campbell; Benjamin L. Campbell (HortScience)
During this study, we explored the consumer preferences for the US rose market using a nationwide online survey. Through conjoint analysis, we evaluated how attributes such as price, origin, vase life, and bloom size influence consumer choice. We found that rose origin is the most significant factor, accounting for 31% of consumer preference, followed by price (23%) and vase life (21%). The US roses are favored over those from Ecuador, Colombia, and other Latin American countries. Price sensitivity is evident, with a preference for roses priced at approximately $9.99 per dozen and a vase life of 14 days. During this study we identified eight distinct consumer segments with varying priorities, including those who value origin, price, vase life, or a combination of these attributes. Market simulation indicates that US rose producers can gain a substantial market share by emphasizing US origin, offering competitive pricing, and enhancing product attributes like bloom size and vase life. The findings suggest that to remain competitive, US rose growers should focus on origin labeling and innovative practices to counteract the influence of international sellers and capitalize on emerging market opportunities.